CHALLENGES OF THE TEACHER IN THE PANDEMIC - Santana de Souza , Tiago (Revista Gênero e Interdisciplinaridade, 2021)
We know that for almost two years we have been facing a very delicate moment that has affected the entire world and different areas of our daily lives. Among them we had stoppage of Industry, culture, commerce and other extremely important areas for us such as education for example. In this way, education had to undergo innovations so that it would not remain paralyzed. The study in question seeks to expose some of the challenges that the pandemic brought to the teacher, so we had as a central theme for this study Challenges Do Professor Na Pandemic. As a methodological support for the construction of this research, we used bibliographical research where we enjoyed articles already published by authors with themes related to our study. Among the main authors we have Andrade, Barbosa, Cardoso, Arruda, Silva and others who contributed to the production of the research in question. Finally, through the data collected and analyzed, it was clear that the teacher had to face and overcome several challenges ranging from lack of resources, adaptation of a new teaching format that required the teacher to have great skills with technologies, and others such as extended working hours, mental fatigue and emotional frailties.